2012
DOI: 10.1152/japplphysiol.01578.2011
|View full text |Cite
|
Sign up to set email alerts
|

Continuum vs. spring network models of airway-parenchymal interdependence

Abstract: The outward tethering forces exerted by the lung parenchyma on the airways embedded within it are potent modulators of the ability of the airway smooth muscle to shorten. Much of our understanding of these tethering forces is based on treating the parenchyma as an elastic continuum; yet, on a small enough scale, the lung parenchyma in two dimensions would seem to be more appropriately described as a discrete spring network. We therefore compared how the forces and displacements in the parenchyma surrounding a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…The results of the present investigation build on our previous modeling studies of airwayparenchymal interdependence in which we showed that the distribution of displacements and forces within the parenchyma surrounding a contracting airway are rather different depending on whether the parenchyma is modeled as a hexagonal network of springs, a triangular network (Ma and Bates, 2012;Ma et al, 2013), or a continuum model (Breen et al, 2012). In all cases the parenchymal distortion is greatest next to the airway wall and decreases with radial distance (Figs.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results of the present investigation build on our previous modeling studies of airwayparenchymal interdependence in which we showed that the distribution of displacements and forces within the parenchyma surrounding a contracting airway are rather different depending on whether the parenchyma is modeled as a hexagonal network of springs, a triangular network (Ma and Bates, 2012;Ma et al, 2013), or a continuum model (Breen et al, 2012). In all cases the parenchymal distortion is greatest next to the airway wall and decreases with radial distance (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…4), similar to the predictions of the Lai-Fook theory (LaiFook, 1979b;Lai-Fook et al, 1977a;Lauzon et al, 1992), which is based on continuum mechanics. We attribute these differences in predicted behavior to the differences in resistance to shear exhibited by the hexagonal versus the triangular spring networks (Ma and Bates, 2012). Without the diagonal struts that form the triangular network, the hexagonal network of springs more easily undergoes shear deformation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We represented the alveolar walls in the parenchyma as pin-joined springs arranged in a repeating hexagonal pattern, as this represents the conventional idealization of the appearance of a thin slice of lung tissue (Mead et al, 1970; Wilson, 1972). We found, somewhat unexpectedly, that such a network produces long-range transmission of forces in response to the distortion produced by the narrowing of the embedded airway (Ma and Bates, 2012; Ma et al, 2013a). By contrast, when the springs are arranged in a repeating triangular pattern, or the parenchyma is represented as an elastic continuum, the elastic forces fall off rapidly with distance from the airway wall (Ma and Bates, 2012), in apparent accord with existing theory about airway-parenchymal interdependence (Lai-Fook, 1979; Wilson, 1972).…”
Section: Introductionmentioning
confidence: 77%
“…We developed custom software based on the finite element method, adapted from our previously described model of airway-parenchymal interdependence, 1821 that solves a system of force equilibrium equations for a planar spring network. 40 Each spring was assumed to be a bar element with baseline length x 0 .…”
Section: Methodsmentioning
confidence: 99%